Lean Six Sigma Black Belt Handbook : Tools and Methods for Process Acceleration - Voehl, Frank, 1946- (CRC Press (an imprint of Taylor & Francis), 2014)
Although Lean and Six Sigma appear to be quite different, when used together they have shown to deliver unprecedented improvements to quality and profitability. The Lean Six Sigma Black Belt Handbook: Tools and Methods for Process Acceleration explains how to integrate these seemingly dissimilar approaches to increase production speed while decreasing variations and costs in your organization. Presenting problem-solving tools you can use to immediately determine the sources of the problems in your organization, the book is based on a recent survey that analyzed Six Sigma tools to determine which are the most beneficial. Although it focuses on the most commonly used tools, it also includes coverage of those used a minimum of two times on every five Six Sigma projects.